2009
DOI: 10.1093/abbs/gmp068
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumor activity and immunological modification of ribosome-inactivating protein (RIP) from <italic>Momordica charantia</italic> by covalent attachment of polyethylene glycol

Abstract: Ribosome-inactivating proteins (RIPs) are a family of enzymes that depurinate rRNA and inhibit protein biosynthesis. Here we report the purification, apoptosis-inducing activity, and polyethylene glycol (PEG) modification of RIP from the bitter melon seeds. The protein has a homogenous N-terminal sequence of NAsp- Val-Ser-Phe-Arg. Moreover, the RIP displayed strong apoptosis-inducing activity and suppressed cancer cell growth. This might be attributed to the activation of caspases-3. To make it available for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 24 publications
1
26
0
1
Order By: Relevance
“…At present, many proteins from different sources have been found to possess antitumor activity (28)(29)(30)(31)(32). Of these, fungal proteins are the major one, in which fungal immunomodulatory protein (FIP), ribosome-inactivating protein (RIP), lectins, and glycoproteins, are involved, due to their favorable effect against a variety of tumors (33).…”
Section: Discussionmentioning
confidence: 99%
“…At present, many proteins from different sources have been found to possess antitumor activity (28)(29)(30)(31)(32). Of these, fungal proteins are the major one, in which fungal immunomodulatory protein (FIP), ribosome-inactivating protein (RIP), lectins, and glycoproteins, are involved, due to their favorable effect against a variety of tumors (33).…”
Section: Discussionmentioning
confidence: 99%
“…However, caspase proteins are recruited during classical apoptosis via the activation of the apoptotic signaling pathway (Vaux et al, 1999). Our previous study indicated that α-MMC and its PEGylated conjugates decreased the proliferation of human epidermal carcinoma A431 cells via caspase 3-dependent apoptosis (Li et al, 2009). The established choriocarcinoma JAR cell line has important advantages for in vitro study, such as homogeneity, a low spontaneous rate of apoptosis, and the practicality of its progression procedures (Gaus et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Natural and modified α-MMC were prepared as described previously (Li et al, 2009). The purification of α-MMC was accomplished in the following four steps: The supernatant was extracted from bitter melon seeds with acetate buffer (50 mM, pH 5.0), followed by ammonium sulfate fractionation precipitation (35 to 70%), MacroCap SP chromatography with a 0 -0.2 M NaCl linear gradient in 20 mM phosphate buffer (PB, pH 7.0) and Superdex 75 chromatography with 20 mM PB containing 0.15 M NaCl, pH 7.0.…”
Section: Preparation Of α-Mmc and Peg20k-α-mmcmentioning
confidence: 99%
See 1 more Smart Citation
“…Administration of MCP30 decreased PC3 human prostate cancer cell growth by the induction of apoptosis in nude mice [71]. Recent studies further indicate that the chemical modification and reduction of ribosome-inactivating protein in BME, significantly reduced its in vivo immunogenicity, but retained its antiproliferative activity as measured by DNA fragmentation and caspase-3 activation [100]. Cucurbitane-type triterpenoids, charantosides, from a methanol extract of the fruits of MC also inhibited mouse skin carcinogenesis induced by 7,12-dimethylbenz[a]anthracene (DMBA) or peroxynitrite plus 12-O-tetradecanoylphorbol-13-acetate (TPA) [45] α-ESA in bitter melon seed oil suppressing the growth of DLD-1 human colon cancer cells by apoptosis induction via lipid peroxidation [101].…”
Section: Anticancer In Vivo Studiesmentioning
confidence: 99%